1991
DOI: 10.7326/0003-4819-114-5-361
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Sedimentation Rate Predicts Early Relapse and Survival in Early-Stage Hodgkin Disease

Abstract: An unexplained elevated ESR after therapy, especially after modern radiotherapy, independent of other factors, strongly suggest the presence of aggressive and resistant Hodgkin disease. An elevated ESR is predictive of early relapse and poor prognosis; its presence justifies early aggressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 10 publications
1
32
0
2
Order By: Relevance
“…The inflammation score predicts both cancer and cardiovascular disease mortality (Godsland et al, 2011). In cancer, ESR has only been studied as a predictor of progression (Henry-Amar et al, 1991;Borre et al, 1997). Bear et al reported that elevated C-reactive protein (CRP) levels were related to poor prognosis in patients with metastatic prostate cancer (Beer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation score predicts both cancer and cardiovascular disease mortality (Godsland et al, 2011). In cancer, ESR has only been studied as a predictor of progression (Henry-Amar et al, 1991;Borre et al, 1997). Bear et al reported that elevated C-reactive protein (CRP) levels were related to poor prognosis in patients with metastatic prostate cancer (Beer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…10 An elevated ESR is also associated with Hodgkin's disease and an elevated ESR after chemotherapy for Hodgkin's disease has been found to be a poor predictor of survival. 11 Patients with collagen vascular diseases, significant infection, or malignancy almost always have symptoms or signs that suggest a more involved or complicated disorder than what is expected in an individual with usual atopy. It is at this point that an ESR, in conjunction with other laboratory tests, may be helpful in supporting a mimicking or complicating disorder.…”
Section: Esr In Allergy/immunologymentioning
confidence: 95%
“…Elevated ESR is a prognostic factor in Hodgkin's disease [43][44][45]. In one study, it has shown significance in univariate analysis for survival in patients with primary gastrointestinal NHL [46].…”
Section: Discussionmentioning
confidence: 99%